2017
DOI: 10.1186/s12977-017-0377-y
|View full text |Cite
|
Sign up to set email alerts
|

More than meets the I: the diverse antiviral and cellular functions of interferon-induced transmembrane proteins

Abstract: The first responders of human antiviral immunity are components of the intrinsic immune response that reside within each and every one of our cells. This cell-autonomous arsenal consists of nucleic acid sensors and antiviral effectors strategically placed by evolution to detect and restrict invading viruses. While some factors are present at baseline to allow for constant surveillance of the cell interior, others are upregulated by cytokines (such as interferons) that signal a viral infection underway in neigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
116
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(121 citation statements)
references
References 85 publications
3
116
0
2
Order By: Relevance
“…The expression of WT IFITM3 had been previously associated with the loss of mature Env incorporation in HIV (37). However, this finding remains controversial, as other studies have not observed such changes in the HIV-1 glycoprotein (16,23,41,42) or for other viral glycoproteins (36), so at present, the reasons for this discrepancy remain unclear. Given that under the experimental conditions used here, no major changes were observed in the amounts of mature Env incorporated into HIV-1 virions upon the expression of the WT or of most IFITM3 mutants, we believe that 85-90 most likely represents a gain-of-function mutant.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…The expression of WT IFITM3 had been previously associated with the loss of mature Env incorporation in HIV (37). However, this finding remains controversial, as other studies have not observed such changes in the HIV-1 glycoprotein (16,23,41,42) or for other viral glycoproteins (36), so at present, the reasons for this discrepancy remain unclear. Given that under the experimental conditions used here, no major changes were observed in the amounts of mature Env incorporated into HIV-1 virions upon the expression of the WT or of most IFITM3 mutants, we believe that 85-90 most likely represents a gain-of-function mutant.…”
Section: Resultsmentioning
confidence: 95%
“…Over the years, several studies raised the possibility that IFITM3 could act by either modulating the intracellular content of cholesterol (during target cell protection) (39) or commandeering a decrease in the amount of mature envelope glycoproteins incorporated into HIV-1 virions (37). However, both of these findings remain debated, as further studies failed to obtain evidence of changes in either intracellular cholesterol levels (31,40) or glycoprotein incorporation upon IFITM expression (16,23,36,41,42).…”
mentioning
confidence: 99%
“…Viral entry is a key target of potent IFN-mediated restriction, specifically by ISGs such as IFITMs, 214 a family of 5 membrane-resident antiviral genes in humans with broad antiviral effects (Shi, Schwartz, & 215 Compton, 2017). IFITMs restrict viruses that enter cells by fusion at the plasma membrane or in the 216 endosome.…”
mentioning
confidence: 99%
“…Furthermore, there is almost no species specificity in antiviral activity of IFITMs [22,23]. For example, primate-derived IFITMs are effective inhibitors of simian immunodeficiency virus (SIV), and primate IFITM3 alleles also exhibit superior anti-HIV activity compared to human IFITM3 [22,24,25]. Amino-terminal mutants of primate IFITM3 are more easily incorporated into HIV virions, resulting in enhanced inhibition of HIV-1 fusion [25].…”
Section: Introductionmentioning
confidence: 99%